2016
DOI: 10.1002/hep.28428
|View full text |Cite
|
Sign up to set email alerts
|

Monoclonal anti‐envelope antibody AP33 protects humanized mice against a patient‐derived hepatitis C virus challenge

Abstract: End-stage liver disease (ESLD) caused by hepatitis C virus (HCV) infection is a major indication for liver transplantation. However, immediately after transplantation, the liver graft of viremic patients universally becomes infected by circulating virus, resulting in accelerated liver disease progression. Currently available direct-acting antiviral therapies have reduced efficacy in patients with ESLD and prophylactic strategies to prevent HCV recurrence are still highly needed. In this study, we compared the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
34
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 58 publications
(180 reference statements)
4
34
0
Order By: Relevance
“…A strong correlation between viral clearance and the induction of an early and broad NAb response following HCV infection has been reported in a number of patient cohorts with HCV infection (6)(7)(8). In addition, in vivo challenge/protection studies have shown that the passive transfer of monoclonal and polyclonal NAbs was able to prevent HCV infection in chimpanzees (9) and in mice (10)(11)(12)(13)(14), highlighting the important role of NAbs in protecting against HCV infection. A single HCV vaccine that could induce NAbs against all seven known HCV genotypes would be ideal.…”
mentioning
confidence: 89%
“…A strong correlation between viral clearance and the induction of an early and broad NAb response following HCV infection has been reported in a number of patient cohorts with HCV infection (6)(7)(8). In addition, in vivo challenge/protection studies have shown that the passive transfer of monoclonal and polyclonal NAbs was able to prevent HCV infection in chimpanzees (9) and in mice (10)(11)(12)(13)(14), highlighting the important role of NAbs in protecting against HCV infection. A single HCV vaccine that could induce NAbs against all seven known HCV genotypes would be ideal.…”
mentioning
confidence: 89%
“…The B5 treatment was initiated 4 days before the animals were challenged with serum-derived HCV and was continued for up to 31 days after injection of the virus. A similar pretreatment approach is usually used to characterize the antiviral activity of entry inhibitors in vivo (53)(54)(55)(56)(57). As shown in Fig.…”
Section: B5 Inhibits Hcv Infectionmentioning
confidence: 99%
“…The supernatant was collected and stored at −80 °C until use. Constructs containing the following viral strains were used: H77, UKN1A20.8, UKN1A14.38, J4, UKN1B5.23, UKN1B12.16, P5VD, P5VE, P5VF, JFH1, UKN2A1.2, UKN2B2.8, S52, UKN4.11.1, UKN5.14.4 and UKN6.5.8 in addition to 28 Belgian isolates (Desombere et al, 2016; Fafi-Kremer et al, 2010; Lavillette et al, 2005; Owsianka et al, 2005). …”
Section: Methodsmentioning
confidence: 99%
“…Polyclonal antibodies from HCV-infected patients were able to protect animal models like humanized mice and chimpanzees from HCV challenge (Bukh et al, 2015; Meuleman et al, 2011; Vanwolleghem et al, 2008). We and others previously reported that neutralizing antibodies targeting the E2 protein could protect from HCV infection in vitro and in vivo (Desombere et al, 2016; Keck et al, 2016; Mesalam et al, 2016). In addition, administration of mAb MBL-HCV1, targeting E2, delayed viral rebound following liver transplantation, while complete protection was reported when combined with the polymerase inhibitor sofosbuvir (Chung et al, 2013; Smith et al, 2017).…”
Section: Introductionmentioning
confidence: 91%